Update on post-traumatic stress syndrome after anesthesia - Aceto, P; Perilli, V; Lai, C; Sacco, T; Ancona, P; Gasperin, E; Sollazzi, L (European review for medical and pharmacological sciences, 2013)
Between 0.5% and 2% of surgical patients undergoing general anesthesia may experience awareness with explicit recall. These patients are at a risk for developing anxiety symptoms which may be transient or can lead to post-traumatic stress disorder (PTSD). The aim of this review was to assess the prevalence of PTSD after intraoperative awareness episodes and analyze patients' complaints, type and timing of assessment used. PubMed, MEDLINE and The Cochrane Library were searched up until October 2012. Prospective and retrospective studies on human adult subjects describing prevalence of PTSD and/or psychological sequalae after awareness episodes were included. Seven studies were identified. Prevalence of PTSD ranged from 0 to 71%. Acute emotions such as fear, panic, inability to communicate and feeling of helplessness were the only patients' complaints that were significantly correlated to psychological sequelae including PTDS. There were cases that reported psychological symptoms after 2-6 hours from awakening (%) or 30 days after (%). Previous studies used psychological scales lacking of dissociation assessment. Whenever an awareness episode is suspected, a psychological assessment with at least three interviews at 2-6 h, 2-36 h and 30 days must be performed in order to collect symptoms associated with both early and delayed retrieval of traumatic event. As a dissociative state could hide the expression of reactive symptoms after intraoperative awareness, future studies should be focused on detecting dissociative symptoms in order to carry out a prompt and appropriate treatment aimed at avoiding long-term psychological disability.